Improving Students’ Comprehension About Pluralism Through Narrative Text - widodo, urip; Subandi, Agus; Suyatno, Tri; Walyono, Walyono (LPPM Universitas PGRI Sumatera Barat, 2022)
This study aims to improve students' understanding of pluralism through narrative texts. This research is a classroom action research conducted on students of class XI IPA 1 at SMA Negeri 1 Sigaluh, Banjarnegara Regency, totaling 34 students. The level of students' understanding of pluralism was measured using a questionnaire. In addition, to strengthen the implementation of narrative texts in the classroom, the researchers conducted observations and interviews. The results of the research before the action were known that 23% of students had a low level of understanding of pluralism, 29% was sufficient, 41% was good, and only 7% or 2 students were in the high category. Furthermore, the questionnaire analysis in cycle 1 showed that students' understanding of pluralism increased significantly where there were no more (0%) students who had a low level of understanding of pluralism, 35% of students had a level of understanding of pluralism that was sufficient, 48% was good, and 17% was high. Furthermore, significant changes occurred in cycle 2 where 8% of students still have a sufficient level of understanding of pluralism, 64% are good, and 26% are high. The increase is inseparable from social values in the form of understanding related to friendship, unity, mutual respect, respect and care for each other which are contained in the various narrative texts given.